Ummat-Ecomap: Strategic analysis of spatial based digital innovation for ziswaf optimization in economic development - Nabila Rajabbilaula; Muhammad Ramdan Ridwanullah (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The size of the population with a majority religion does not make an area prosperous. As a city with a Muslim population of 98.5%, Tasikmalaya—also known as the city of waqf—still faces socio-economic contradictions in the form of high poverty and unemployment rates. The potential for Zakat, Infak, Sedekah, and Wakaf (ZISWAF) funds in this region is enormous, but their contribution to poverty alleviation has not been optimal due to conventional management patterns that are not based on accurate data. Although previous studies have shown the strategic role of Islamic philanthropy in economic empowerment, its effectiveness is often hampered by limited transparency and minimal use of spatial data. Therefore, this study aims to formulate the UMMAT-EcoMap concept as a digital instrument to optimize the strategic and sustainable distribution of ZISWAF. Methods: This study uses descriptive qualitative approach with a literature review design combined with spatial analysis. The analytical framework integrates Geographic Information Systems (GIS) and unbalanced growth theory to map pockets of poverty, regional characteristics, and the potential of relevant local economic sectors as targets for ZISWAF utilization. Findings: The results show that UMMAT-EcoMap enables increased accuracy in ZISWAF distribution through real-time mapping based on welfare indicators and sectoral potential. In line with Hirschman's theory, this approach has the potential to create growth poles in leading sectors supported by ZISWAF funds, thereby promoting economic spillover effects for other supporting sectors and regions. Conclusion: UMMAT-EcoMap is a strategic innovation that synergizes spatial analysis with Islamic philanthropy governance, thereby increasing the effectiveness, transparency, and impact of ZISWAF in accelerating poverty alleviation in Tasikmalaya. Novelty/Originality of this article: The novelty of this research lies in the integration of Geographic Information Systems (GIS) with Unbalanced Growth Theory (Hirschman’s Theory) to transform Islamic philanthropy (ZISWAF) management.